MODEL PENGELOLAAN PRAKTIK PENGALAMAN LAPANGAN PADA MASA PANDEMI - Ramdanil Mubarok (Institut Agama Islam Negeri (IAIN) Palopo, 2020)
Field experience practice is one of the curricular activities carried out by students, and is a compulsory course for every student of the PAI study program, which includes teaching exercises and non-teaching assignments in a guided and integrated manner. but, due to the covid-19 pandemic, field experience implementation is different from usual, therefore what is the model for managing the field experience of the PAI study program during the pandemic?. This study aims to determine the management model of field experience in the PAI study program during the pandemic with the hope that it can be a reference for continuing to practice field experience even during the pandemic period. The research method used is qualitative research methods. The result is that the management model of field experience in the PAI study program during the pandemic cannot be separated from the management function, namely planning, organizing, implementing, and monitoring. In practice, it is not much different from the implementation of field experience practice (PPL) in general, except in the location of the implementation so that there is no involvement of civil servant teachers in teaching practice.